UPAYA PENCEGAHAN PENYAKIT DIABETES MELITUS MELALUI PENDEKATAN KELUARGA - Wardani, N.W.S.; Slamet, I.K. (Buletin Udayana Mengabdi, 2024)
Diabetes Mellitus lead a health problem due to its increasing prevalence and is one of the most common cause of death. Based on WHO, 422 million people in the world suffer from Diabetes Mellitus and it causes 1.5 million deaths each year. Diabetes also causes complications of heart attacks, stroke, retinal disorders and blindness, foot gangrene and amputation, end-stage kidney disease and sexual dysfunction. These complications are classified as catastrophic diseases and require high costs for treatment, it becomes necessary to implement both primary and secondary prevention. This PKM aims to increase the knowledge of PKK in Banjar Tubuh, Batubulan Sukawati Gianyar in preventing DM.This PKM was held on December 5, 2023 at Balai Banjar Tubuh, Batubulan Sukawati Gianyar, using a lecture approach and interactive dialogue with PKK women about Diabetes Mellitus and its prevention. The average age was 43.63 years, with 78.2% of participants having a high school education or above. Most were employed outside the home, contributing to family finances. The pretest score was 52.82, and following the PKM activity, the posttest score increased to 91.28, resulting in a 72.1% knowledge improvement among PKK mothers regarding Diabetes Mellitus prevention.